HUBUNGAN GANGGUAN PERHATIAN DENGAN KOGNITIF ANAK ADHD - Diva Angraini (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2023)
This article is motivated by finding various studies in articles and journals regarding an ADHD child who has attention disorders and cognitive impairment, and how attention and cognitive problems exist in ADHD children. ADHD children experience difficulties in paying attention, their emotions, including in cognitive matters. The method used in writing this article is a literature review, with the subject of the article being children with ADHD. ADHD children who experience attention disorders tend to be disturbed in their cognition, for example, children lack focus in learning which comes from various factors, one of which is difficult for the child to focus attention. So that it can cause concentration in learning to decrease when learning takes place. Concentration in learning is very important when learning takes place, children who are said to concentrate on learning like children are able to pay attention to the teacher while explaining, listen, ask questions while studying, respond, understand the material, answer questions correctly, re-inform the knowledge gained to others , Lack of concentration in learning will affect the low learning achievement in children